Realization of Control System of Automatic Welding Machine for Air Conditioning Flange Based on CANopen. Issue 1 (1st March 2022) - Ren, Kailang; Yan, Liangwen; Huang, Shan; Dong, Xudong; Wei, Mingsen; Chen, Jiajian
Abstract: The principle of automatic welding machine (AWM) for air conditioning flange is introduced. The architecture of the control system of AWM realizes the multi spindle linkage control. The communication between PLC and servo driver is built based on CANopen protocol, and the communication between PLC and touch screen is set up based on Modbus RTU protocol. To meet the welding machine spindle coordination control requirements, the PLC program is designed by Delta ISPsoft programming software, and simplified by the application of sequential function chart (SFC) and function block. The human machine interaction (HMI) is developed by Xinjie Touchwin. Linear interpolation algorithm (LIA) is used to prevent the welding defects on the air conditioning flange corner thus it improves the welding quality and realizes the straight path of welding torch from the original to starting welding point and from the end welding point to the original simultaneously. The AWM for air conditioning flange can replace the manual welding and has a broad application prospect in many areas.